Bioactive polymeric–ceramic hybrid 3D scaffold for application in bone tissue regeneration - Torres, Ana (2018)
Submitted by Ilídio Correia (icorreia@ubi.pt) on 2018-03-19T18:00:50Z No. of bitstreams: 1 2013 Torres MSEC.pdf: 2367789 bytes, checksum: 372aabccab26df29a217f17d68cb63d3 (MD5)